Percepção dos produtores rurais da região de Sete Lagoas, MG, sobre o meio ambiente, 2008-2009 - Fernanda Lusmara de Menezes (2010)
The intervention on the environment triggered by agricultural production has serious consequences to the health of individuals. This descriptive study has as its main objective to indentify the perception of farmers in relation to the environment. It was realized 68 interviews with dairy farmers of Regional Cooperative of Rural Producers of Sete Lagoas, Minas Gerais. The responses were evaluated for the frequencies in to software Epi Info 6.04. It was found that only 47% used some form of water treatment before consumption. The manure is applied directly on crops (19%). Among participants 40% burned household waste from the property. The use of chemical products in the production was related by 51.5% the participants and 44.7% use them without defined periodicity. About the management of soil, 96% uses level curves and only 4.5% employ the practice to burn the properties. About environmental change 39% reported the change in distribution of rains and 29% observed increase in temperature in the region. Of the participants, 31% said that climate change reduces the areas of crops and 13.5% noted that there is decrease in milk production. It was found that some practices by participants are inadequate and the farmers need more information on waste management and use of natural resources.